Optimization of WEDM Process Parameters for Cutting Speed using Taguchi technique. (2019) - Muniappan, A.; Jayakumar, V.; Ajithkumar, R.; Veerabhadra, S.K.; Prasanna, R.
Abstract: In this present experimental study, the effect and advancement of machining parameters on cutting speed in wire electrical discharge machining (WEDM) operations were studied. The hybrid metal matrix composite (MMC) was manufactured by process named as stir casting utilizing particulates of Silicon carbide and graphite each in Al6061 combination. The analyses were outlined with Taguchi L27 design matrix. WEDM parameters resemble pulse (PU) on time, current, PU off time, gapset voltage, wire tension and wire feed are considered. The impact of parameters on the cutting speed (CS) is dictated by utilizing examination of fluctuation. The optimized parameters are PU on time (Level 3), PU off time (Level 1), peak current (Level 2), gap set voltage (Level 1), wire feed (Level 3) and wire tension (Level 2) are the best combination to achieve best cutting speed. PU off time, set voltage, PU on time and discharge current have considerable effect and most influenced control parameters on CS